Effectiveness of prevention and treatment of disorders in the menopause in women with hyperproliferative processes of reproductive system - Л. І. Бутіна (Publishing House TRILIST, 2018)
Objective. Evaluate the effectiveness of prevention and treatment of disorders in menopausal women with hyperproliferative processes of reproductive system (HPPRS). Materials and methods. The substitutive hormone prevention (SHP) of neurovegetative and psycho-emotional disorders in menopause (NVPDM) was conducted among 184 women aged 40 to 53 with the signs of HPPRS according to the data of ultrasound uterine and the results of histological investigations of mucosal scrapings of the uterus. The women were divided into main group and 4 comparison group. For the prevention into main group the appointment of combine oestrogen-gestogen preparation with composition of valerat of estradiol and dienogest and into comparison group - oestrogen-gestogen preparation with composition of ethinyl estradiol and dienogest drug according to the contraceptive scheme. The treatment was performed in 193 women after SHP of NVPDM, and in 31 women after naturally menopause, and 4 comparison group. The treatment was performed the appointment of the complex of preparations: a combined vegetable of preparation, a preparation from the microalgae Spirulina platensis, apple pictine and an anxiolytic agent with theactiv substance mebicar. Results of the study. After SHP in 24 women of the main group (n = 60) the menstrual function was recovered and the symptoms of NVPDM disappeared. The intensity of the symptoms of NVPDM corresponds to the middle degree of the course of disorders in menopause. After treatment the intensity of NVPDM declines and MIK in women after the usage of our medical prognostication complex became in 2.5 times less than before treatment, in women with natural menopause MIK became in 2.1 times less than before treatment. Conclusion. The using of the method of prevention and treatment allows to the prevention of NVPDM was performed among 40% of women and reduce the intensity of NVPDM in 2.5 times on the account of the decline of the gonadotropins level as compared with healthy women.